2023
DOI: 10.1177/21501319231164910
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Primary Care Clinicians’ Perspectives on 2021 New and Updated Cancer Screening Guidelines

Abstract: Background and Objective: Cancer screening rates remain low in rural, racial and ethnic minority, low-income, and uninsured populations. Prior studies showed that cancer screening recommendations vary based on clinicians’ factors. We conducted an exploratory study on primary care clinicians’ beliefs about new or updated cancer screening guidelines according to clinician demographics. Methods: This cross-sectional study involved administering a web-based survey in July and August of 2021 to primary care clinici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Angier et al 18 recently reported 81 responding primary care clinicians’ understanding of new and updated screening guidelines. They found that 86.4% and 57.8% of male and female clinicians, respectively, recognized that LCS prevented early cancer mortality, and 33.3% of clinicians were unaware of the expanded 2021 USPSTF LCS guidelines.…”
Section: Barriers Clinicians Face In Providing Lcsmentioning
confidence: 99%
“…Angier et al 18 recently reported 81 responding primary care clinicians’ understanding of new and updated screening guidelines. They found that 86.4% and 57.8% of male and female clinicians, respectively, recognized that LCS prevented early cancer mortality, and 33.3% of clinicians were unaware of the expanded 2021 USPSTF LCS guidelines.…”
Section: Barriers Clinicians Face In Providing Lcsmentioning
confidence: 99%